(untitled) (Global Journal of Human-Social Science, 2016)
The author of the following article will describe the features of the proverbial phraseologies of the French, Uzbek and Russian languages. The subject has not been studied in detail by the Uzbek linguists yet, i.e. it hasn’t been compared with the languages that belong to different families. The article will make constructive comments for the terms in three languages comparing and revealing their equivalents, which will be referred as proverbial phraseology.